Novel blood pressure-lowering effect of spathulenol in rats - Raslan Ain-Fatin; Yee, Yong Mei; Hoe, See Ziau; Ong, Hooi Tin; Lam, Sau Kuen (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, natural compounds from plant sources are sought after as alternative anti-hypertensive treatments. Spathulenol (Spa), a terpenoid plant metabolite obtained mainly from the Origanum species has shown anecdotal evidence of blood pressure (BP)-lowering properties probably through the effects on vasoreactivity. This study aimed to investigate the BP-lowering activities of Spa in vivo as well as to ascertain the mechanisms of action in vitro. Male Sprague-Dawley (SD) rats (n=16) and spontaneously hypertensive rats (SHR) (n=16) with their normotensive WistarKyoto (WKY) rats (n=16) as controls were subjected to anaesthesia and administered intravenous boluses of Spa at 0.0, 0.045, 0.90, 0.18, 0.36, and 0.7 mg/kg or positive control losartan at 0.0, 0.6, 1.2, 1.8, 2.4 and 3.0 mg/kg. The BP and heart rate (HR) of the rats were recorded by a computerised physiographical system (Power Lab) through carotid arterial cannulation that was connected to a pressure transducer. The data were analysed by using the Lab Chart 6 software. Spathulenol was also tested for angiotensin-converting enzyme (ACE) inhibitory activity by using the ACE1 inhibitor screening kit (PromoKine). Spathulenol was able to decrease the BP of rats in a dose-dependent manner with the BPlowering effect being significantly (p<0.05) higher in the SHRs than in the WKY controls. Furthermore, Spa was able to inhibit the ACE activity suggesting the possibility that this could be one of the mechanisms underlying the observed BP-lowering effect.